A Case of Mature Cystic Teratoma Arising from the Fourth Ventricle - Parikshit Sanyal; Sanghita Barui; Smriti Mathur; Utpal Basak (Hindawi Limited, 2013)
Intracranial teratomas represent a rare lesion accounting for 0.1%-0.7% of all intracranial tumors. Those in the fourth ventricle have rarely been reported. The present case is that of a 28-year-old man with occipital headache for two months. MRI examination revealed a well-defined extra-axial cystic lesion in posterior fossa in the midline herniating through the foramen magnum. Pre operatively, the mass was seen to be occupying the whole of the posterior fossa and arising from the roof of the fourth ventricle. On gross examination, the lesion had both solid and cystic components. Histopathological examination showed multiple cystic areas lined by brain tissue admixed with islands of cartilage and salivary gland elements and intestinal type glands. A diagnosis of mature cystic teratoma was made.